Rola duszy rozumnej w antropologii duchowej Orygenesa - Szram, Mariusz (Verbum Vitae, 2022)
Origen’s teaching about the soul, like all his theology, is hypothetical-exploratory. The goal of the article is to extract and gather together the key concepts from Origen’s works dealing with the rational soul and its role in the human person. Origen placed his considerations on anthropology in the context of Christian spiritual life, but he did not treat them as purely philosophical distinctions, despite referring to the philosophy of Middle Platonism and Philo of Alexandria. The comparative analysis of Origen’s texts, as preserved in the original Greek or early Christian Latin translations, highlights the main themes of his spiritual anthropology: the trichotomous division of the structure of the human person; ascribing the category of the “image of God” in man to a rational soul; and the soul’s striving to fully surrender to the Holy Spirit, i.e. to achieve a state of perfect likeness to God. In the light of Origen’s statements, the rational soul – also known as the mind, heart, and guiding principle – is an essential structural element of the human person, identical to the image of God in man. In earthly life, she wages a spiritual battle against the desires of the flesh, trying to subordinate the whole person to the spirit, and, through it, to the Holy Spirit.